2021
DOI: 10.1093/burnst/tkab021
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin preconditioning enhances the efficacy of adipose-derived mesenchymal stem cells to accelerate healing of burn wounds

Abstract: Background Following recent findings from our group that curcumin preconditioning augments the therapeutic efficacy of adipose-derived stem cells in the healing of diabetic wounds in rats, we aimed to investigate the regenerative effects of curcumin preconditioned adipose-derived mesenchymal stem cells (ASCs) for better recovery of acid inflicted burns in this study. Methods ASCs were preconditioned with 5 μM curcumin for 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 64 publications
1
10
0
2
Order By: Relevance
“…Many studies concern the use of polyphenol in copresence with stem cells for targeting therapeutic application [ 13 ]. Curcumin formulations constitute suitable candidates [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Indeed, curcumin therapy increasingly seems an attractive alternative in patients with contraindication to non-steroidal anti-inflammatory drugs (NSAIDs) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies concern the use of polyphenol in copresence with stem cells for targeting therapeutic application [ 13 ]. Curcumin formulations constitute suitable candidates [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Indeed, curcumin therapy increasingly seems an attractive alternative in patients with contraindication to non-steroidal anti-inflammatory drugs (NSAIDs) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, liposomal Cur has been demonstrated to enhance the activity of endothelial-differentiated-human periodontal ligament stem cells and dental pulp stem cells as an anti-inflammatory strategy [ 44 , 45 ]. In addition, Cur pretreated ADSCs can accelerate the re-epithelialization and angiogenesis of acid inflicted burn wounds [ 46 ]. Here, we demonstrated that Cur reduced AGE-induced AGER and caspase-3 expression, ROS production, apoptosis and NF-κB p65 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin-preconditioned ADSCs had an increased capacity for migration, proliferation, and paracrine potential, suppressed secretion of pro-inflammatory cytokines, and improved healing in comparison with innate ADSCs [ 52 ]. In a rat burn model, autologous ADSCs were seeded in a PRP matrix and injected under the meshed skin graft to improve healing and neovascularization [ 70 ].…”
Section: Methodsmentioning
confidence: 99%